Bone mineral density of Brazilian girls with juvenile dermatomyositis - Castro,T.C.M. de (2005)
We measured bone mineral density (BMD) in girls with juvenile dermatomyositis (JDM) considering multiple factors in order to determine if it could be used as a predictor of reduction in bone mass. A cross-sectional study of lumbar spine BMD (L2-L4) was conducted on 10 girls aged 7-16 years with JDM. A group of 20 age-matched healthy girls was used as control. Lumbar spine BMD was measured by dual-energy X-ray absorptiometry. Weight, height and pubertal Tanner stage were determined in all patients and controls. Duration of disease and mean daily and cumulative steroid doses were calculated for all patients on the basis of their medical charts. JDM activity was determined on the basis of the presence of muscle weakness, cutaneous vasculitis and/or elevation of serum concentration of one or more skeletal muscle enzymes. Seven patients demonstrated osteopenia or osteoporosis. Lumbar BMD was significantly lower in the JDM patients than the age-matched healthy control girls (0.712 vs 0.878, respectively; Student t-test, P = 0.041). No significant correlation between BMD and age, height, Tanner stage, disease duration, corticosteroid use, or disease activity was observed in JDM girls, but a correlation was observed between BMD and weight (Pearson's correlation coefficient, r = 0.802). Patients with JDM may be at risk for a significant reduction in BMD that might contribute to further skeletal fragility. Our results suggest that reduced bone mass in JDM may be related to other intrinsic mechanisms in addition to steroid treatment and some aspects of the disease itself may contribute to this condition.